Significados atribuidos al apoyo familiar y posibles cambios en el proyecto vital de un grupo de jóvenes habitantes de calle (2019)
This study was carried out with the collaboration of a group of five young street dwellers in the city of Bogotá and Soacha. The unstructured interview was used as an investigative method. The interviews were transcribed literally and an inductive categorical analysis was carried out. Similarities and differences between participants were contrasted. There appear categories such as experiences associated with consumption, influence of peers and changes in the life project of each of the participants. It was evidenced that each family had difficulties in terms of communication, parenting patterns, norms, limits. Inside their homes there was intrafamily violence and consumption of SPA, which led these young people to easily influence their peers and end up making the street their home.